Analisis Kelayakan Finansial pada Industri Baglog Jamur untuk Peningkatan Produksi 30.000 Unit per Bulan pada Agroindustri - Imam Agus Prabowo; Mathilda Sri Lestari; Rian Prasetyo (Jurnal Optimalisasi, 2023)
The agricultural sector is the main structure of national economic development. One of the sub-sectors in agriculture that has an important role for the welfare of farmers and the regional economy as well as the national economy is the Horticulture sub-sector. This sub-sector has been supported by the agro-industry. One of the products from this agro-industry is baglog of mushrooms. This study aims to analyze the financial feasibility of increasing production capacity from 20,000 to 30,000 baglogs of mushrooms per month. It caused the average demand is 29,070 baglogs of mushrooms per month. The research object is the manufacture of mushroom baglog. Descriptive quantitative with financial feasibility analysis techniques and sensitivity analysis is used as a method in this research. The results found that the investment period of 5 years required an investment cost of IDR 244,342,677. Financial feasibility analysis with a discount rate of 9% produces an NPV value of IDR 257,886,281, an IRR of 44.594%, a Profitability index of 2.06 and a Payback Period of 1.88 years. The results of the sensitivity analysis of an increase in the cost of raw materials by 17% and a decrease in production of 9% obtained the results of NPV > 0, IRR > 9%, Profitability index > 1 and Payback period < business life. Based on these results, the investment is financially feasible because IRR > MARR.